Using the method of impedance cardiography in cases Off-pump coronary artery bypass graft (CABG) surgery - N. Ioffe; K. Yaschuk; K. Danilevskaya; S. Rudenko; R. Vitovsky (Ukrainian Journal of Cardiovascular Surgery, 2017)
The data on impedance cardiography, its diagnostic value and possible different applications suggest that it may also be very useful in cases Off-pump coronary artery bypass graft (CABG) surgery.Impedance cardiography is non-invasive, which is of a particular advantage over the conventional methods that require catheterization. As a result, the patient is not at risk of possible complications and the procedure is less expensive.The test involves placing, on the skin of the patient, the output electrodes to apply high-frequency low-intensity alternating current to the patient’s chest, and the receiving electrodes to record voltage variations and obtain electrocardiography (ECG) recording.Various authors report that attempts have been continued to compare the results from ICG and those obtained by other diagnostic methods.In cases Off-pump coronary artery bypass graft (CABG) surgery Impedance cardiography is good opportunity to establish hemodinamics, manage the fluid level a patient, trend and detect hemodynamic changes during the operation.